Organizational Memory Dysfunction and the Dynamics of Regional-Owned Enterprise Governance: a Policy Analysis of Traditional Market Fire Mitigation in Pematangsiantar City - Rindu Erwin Marpaung; Kevin William Andri Siahaan; Irwan Irwan; Abather Rahi Saadoon (Tinta Emas Publisher, 2026)
Repeated fires in public facilities are a clear indicator of the fragility of public sector risk management at the regional level. This study aims to evaluate the dysfunction of organizational memory and local government governance through a longitudinal study of a series of traditional market fires in Pematangsiantar City, specifically Dwikora Market (2011, 2014, 2026) and Horas Market (2024). Using a qualitative approach with evaluative methods, data collection was conducted through in-depth interviews, document studies of the financial reports of the Horas Jaya Market Regional Company (PD. PHJ), Mayoral Decrees, and physical spatial observations in the post-disaster area.The study refutes the hypothesis of job rotation disruption, and instead finds a deliberate ignorance by PD. PHJ management, where the 2024 post-fire mitigation recommendations were not followed up with a specific electricity audit. An extreme governance paradox exists: PD. PHJ was able to record revenue of up to Rp 6.38 billion in 2025 from daily levies on traders of Rp 8,000–Rp 30,000, yet spent more than 85% of its operational budget on personnel expenses, thus sacrificing the procurement of vital protection facilities such as hydrants. This crisis was exacerbated by the Pematangsiantar City Government's legislative negligence in allowing Regional Regulation No. 5 of 2014 to expire. The executive's emergency response was also proven to be reactive ( policy by pressure ) because it was only rolled out after it went viral on social media, and suffered from a physical infrastructure bias without touching on efforts to save traders' finances.